(untitled) (International Seven Journal of Multidisciplinary, 2026)
The present study consists of a narrative literature review aimed at discussing maxillary sinus lift techniques, their clinical indications, and the criteria for rehabilitation of atrophic maxillae. Tooth loss in the posterior maxillary region, combined with maxillary sinus pneumatization, results in insufficient bone volume for implant placement, making sinus floor elevation a fundamental and predictable surgical technique. The methodology was based on a search in the PubMed database, selecting articles published in the last five years in Portuguese and English. The results indicate that the choice between the lateral window technique and the transcrestal approach should be based on residual bone height, with the lateral approach indicated for remnants smaller than 4 to 5 mm. Technological advances are highlighted, particularly the osseodensification technique and the use of piezoelectric devices to reduce complications, such as perforation of the Schneiderian membrane. Regarding biomaterials, although autogenous bone remains the gold standard, xenografts and the use of platelet concentrates (L-PRF) show excellent results in accelerating new bone formation and healing. It is concluded that maxillary sinus lift is a safe procedure when preceded by careful three-dimensional planning, enabling satisfactory functional rehabilitation in patients with severe maxillary atrophy.